iPad For Seniors For Dummies, 11th Edition - Spivey, Dwight (--For dummies., 2018)
Get caught up with the latest iPad features An iPad can be so many things: an entertainment hub, a way to stay in touch with the world, a productivity tool, and many other things. iPad For Seniors For Dummies focuses on helping iPad users who are experienced in life-but not in technology. In this friendly, easy-to-follow guide, you'll find out how to fire up any model of iPad, connect to the internet, and use applications to play games, watch movies, listen to music, chat via video, update your social accounts, read the news, or just about anything else you'd want to do. Teach your iPad to answer your commands Stay connected with email, social apps, and video chat Cue up music and movies Find endless ways to let your iPad entertain you If you're anywhere from 50 to 100 and want to find accessible guidance on making the most of your iPad, you're in good hands!